2019
DOI: 10.4314/ahs.v19i3.10
|View full text |Cite
|
Sign up to set email alerts
|

C - reactive protein of cerebrospinal fluid, as a sensitive approach for diagnosis of neonatal meningitis

Abstract: Background: Meningitis, is a potentially life-threatening condition that can rapidly progress to permanent brain damage, neurologic problems, and even death. Bacteria and viruses cause the great majority of meningitis disease in infants and children. CRP is used mainly as a marker of inflammation.Objective: This study was conducted to assess the diagnostic value of CSF-CRP levels for differentiating between septic (bacterial) and aseptic infantile meningitis.Methods: 49 hospitalized infants aged less than two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Studies performed by Dashti and coworkers 15 and Javadinia and coworkers 44 , found that CRP levels were elevated in cases of bacterial meningitis which agree with the current study.…”
Section: Discussionsupporting
confidence: 93%
“…Studies performed by Dashti and coworkers 15 and Javadinia and coworkers 44 , found that CRP levels were elevated in cases of bacterial meningitis which agree with the current study.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies suggested that both CRP, IL-6 and IL-1β are potentially helpful in the diagnosis of bacterial meningitis. 7 , 8 , 16 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 Sample sizes in these studies were often small and populations were not representable for clinical practice. Our study confirms that these results stay robust in a clinically representative population and after validation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, normative ranges were derived from studies on nearly asymptomatic neonates, but these values cannot be used as thresholds for diagnosing bacterial meningitis in symptomatic neonates 18 . Newer CSF biomarkers have been evaluated in a limited number of studies, but these are not yet ready for introduction in clinical practice [19][20][21][22][23][24] .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…18 Newer CSF biomarkers have been evaluated in a limited number of studies, but these are not yet ready for introduction in clinical practice. 19 20 21 22 23 24…”
mentioning
confidence: 99%
See 1 more Smart Citation